2022
DOI: 10.3390/jcm11216590
|View full text |Cite
|
Sign up to set email alerts
|

PSMA Expression in Solid Tumors beyond the Prostate Gland: Ready for Theranostic Applications?

Abstract: In the past decades, the expanding use of prostate-specific membrane antigen (PSMA) imaging for prostate cancer has led to the incidental detection of a lot of extra-prostatic malignancies showing an increased uptake of PSMA. Due to these incidental findings, the increasing amount of immunohistochemistry studies and the deeper knowledge of the mechanisms of expression of this antigen, it is now clear that “PSMA” is a misnomer, since it is not specific to the prostate gland. Nevertheless, this lack of specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 116 publications
0
16
0
Order By: Relevance
“…9 Morphological anatomy is well established in CT and MRI, but these modalities have a limited role in differentiating between fibrosis and viable tumor in postoperative/RT cases. 24 Over the past decade, several studies have shown that PSMA is expressed by a number of malignant tumors other than prostate such as sarcoma, follicular lymphoma, brain tumors, and carcinoma of the breast, lung, kidney, thyroid, and liver. [17][18][19] PSMA, labeled with 68 Ga and 177 Lu, has been used for diagnostic and therapeutic purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Morphological anatomy is well established in CT and MRI, but these modalities have a limited role in differentiating between fibrosis and viable tumor in postoperative/RT cases. 24 Over the past decade, several studies have shown that PSMA is expressed by a number of malignant tumors other than prostate such as sarcoma, follicular lymphoma, brain tumors, and carcinoma of the breast, lung, kidney, thyroid, and liver. [17][18][19] PSMA, labeled with 68 Ga and 177 Lu, has been used for diagnostic and therapeutic purpose.…”
Section: Discussionmentioning
confidence: 99%
“…However, guidelines of clinical management and treatment of metastatic AdCC are not well established 9 . Morphological anatomy is well established in CT and MRI, but these modalities have a limited role in differentiating between fibrosis and viable tumor in postoperative/RT cases 24 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in PC, PSMA overexpression has been identified in various other tumor types, such as glioblastoma or hepatocellular carcinoma (HCC), making them potential candidates for 68 Ga-PSMA-11 imaging and 177 Lu-PSMA-617 treatment [53]. Pilot studies in patients with HCC demonstrated significant uptake in seven patients with multiple liver lesions.…”
Section: Radiotracers Based On Sstr2 Antagonistsmentioning
confidence: 99%
“…Histology after surgical resection reveals a hemangioma. Focal intense PSMA activity in a lung lesion is suggestive of metastatic disease from prostate cancer; however, a variety of benign and nonprostatic neoplasms have demonstrated increased PSMA expression that leads to abnormal findings on PSMA PET/CT images, [1][2][3][4] including primary lung cancer that may have intense PSMA uptake 5 and usually has intense FDG uptake, whereas benign lung neoplasms frequently show minimal FDG uptake. Pulmonary hemangioma is a rare disease that is occasionally found by diagnostic CT. 6,7 There are cases reported for abnormal PSMA uptake in vertebral, 8 liver, 9 or splenic hemangioma.…”
mentioning
confidence: 99%